Trajectories of Physical Aggression Among Hispanic Urban Adolescents and Young Adults: An Application of Latent Trajectory Modeling from Ages 12 to 18 - Maldonado-Molina, Mildred M. (American journal of criminal justice, 2010)
This study sought to identify trajectories of physical aggression among urban Hispanic youth, and to examine the effects of risk and protective factors at age 11 on trajectories of physical aggression over time (ages 12–18). Relying on data from 731 urban Hispanic adolescents from Project Northland Chicago (PNC), latent trajectory modeling was used to determine the number of trajectories, and multinomial logistic regression was used to identify the predictors associated with trajectory membership. The results suggested five trajectories of physical aggression (non-aggressive, low stable, escalators, early-rapid desistors, and high aggression/moderate desistors). After adjusting for several risk and protective factors, language preference (e.g. speaking Spanish at home) was identified as a protective factor, while indirect exposure to alcohol, sadness/depression, fewer negative alcohol-related attitudes, and threatening to fight were associated with increased risk for physical aggression. Study implications indicate that early, multilevel prevention efforts are necessary to deter the initiation and promote the desistance of physical aggression over time among urban Hispanic adolescents.